Development of an Illustrated Storybook to Enhance Prosocial Behaviour in 5-6 Year-Old Children - Setyaningsih, Ani; Sukiman, Sukiman (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The tendency of conventional textbooks with prosocial behavior themes, which mostly contain text or unattractive visual designs, makes reading activities less appealing to children. Illustrated storybooks with creative and locally relevant settings tend to attract students, especially 5-6-year-olds. This study aims to develop a storybook that fosters prosocial behavior in children. Conducted at Fitrah Semesta Kindergarten using the R&D method with the ADDIE model (up to the development stage), the study produced a 10-page storybook. Data analysis employed qualitative and quantitative techniques. The results show that the illustrated storybook received "highly feasible" ratings from material, language, and media experts. Material aspects scored 85.5%, language 89.2%, and media 84.2%, with an average expert rating of 86.3%. Observational responses scored 86.36% (highly feasible), and the pre-test to post-test improvement was 40.36%. This indicates the storybook significantly enhances prosocial behavior and is highly suitable for 5-6-year-olds.